DEVELOPING INTERACTIVE MULTIMEDIA-BASED ESP TO IMPROVE ENGLISH PROFICIENCY AND CAREER GUIDANCE AT UPMI MEDAN - Stevani, Margaret; Yanti, Novi; Hidayat, Ikhwan Mahfud; Laia, Firman Daris; Halawa, Alkisah Ikhlas (English Review: Journal of English Education, 2024)
This research explored the development of an interactive multimedia-based English for Specific Purposes (ESP) program designed to enhance English proficiency and career guidance at UPMI Medan. It addressed a notable discrepancy between theoretical frameworks and practical needs in ESP, as students increasingly demanded courses that integrated both oral and written communication skills with job-related tasks. Applying the Kemp instructional design model, the research used a comprehensive multi-phase approach: assessing student proficiency levels, identifying instructional needs, designing tailored ESP content for Business Administration, Tourism, and Public Speaking, and incorporating multimedia platforms such as Udemy and Gaminik. Key findings revealed that 40% of students prioritized mastering business correspondence, 58% sought improved communication skills for meetings, and 48% were interested in tourism-specific English. The research highlighted the effectiveness of flipped learning and interactive multimedia in overcoming vocabulary challenges and boosting engagement. Ultimately, it emphasized the need to integrate career-focused modules into ESP courses to better align language skills with career aspirations, thereby enhancing employability and professional readiness.